2000
DOI: 10.2134/jeq2000.00472425002900040013x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Leachability of Land‐Disposed Dredged Sediments

Abstract: The potential risk of surface and ground water contamination by trace metals leached from contaminated land disposed dredged sediment is a major environmental concern. The objective of this study was to evaluate trace metal leachability, leachate quality and environmental impacts of land-disposed dredged sediments. In addition to chemical characterization and determination of potential and actual leachability, dredged sediments were also subjected to solid phase fractionation using a sequential extraction proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…However, metal movement occurs and metals leaching through the soil could contaminate groundwater (Reynolds et al, 2002;Emmerich, 1982;Singh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, metal movement occurs and metals leaching through the soil could contaminate groundwater (Reynolds et al, 2002;Emmerich, 1982;Singh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers performed water extractions during sediment ripening (Singh et al, 2000;Stephens et al, 2001) or monitored porewater composition (Prokop et al, 2003). Although this approach is useful to assess the medium-term (up to several months) mobility of metals, it is not adequate when a quick decision has to be made concerning the potential impact of dredging and land-disposal of polluted sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of heavy metals availability and their potential uptake for crops can have possible phytotoxicity effects and dangerous consequences in the food chain. Singh et al [35] observed that potential leachability, defined as the maximum metal pool that may become available for leaching at a constant pH 4, decreased in the following order: Zn~Cd > Mn > Ni > Co > Cu~As > Pb > Cr.…”
Section: The Agronomic Quality Indicatorsmentioning
confidence: 99%